Evaluation of repeatability for the automatic estimation of endothelial cell density in donor corneas. Issue 9 (12th April 2007) - Ruggeri, Alfredo; Grisan, Enrico; Schroeter, Jan
Abstract : Background/Aims: The repeatability of an automatic system for estimation of endothelial cell density (ECD) from microscopy images in donor corneas was assessed. Methods: A computer program for the automatic ECD estimation from frequency analysis was previously presented. An evaluation of its repeatability was performed on a data set containing 200 corneas by assessing the accuracy and precision of automatic versus manual values. For each cornea, 2–21 images (1536 total) at 100× for automatic ECD and one image at 200× for manual ECD were available. Results: Accuracy of automatic ECDs was −45 (SD 99) cells/mm 2 (−2% (4%)). Precision of repeated automatic ECDs on the same cornea was 62 (30) cells/mm 2 (3% (1%)). The algorithm was also capable of identifying all non-processable images. Conclusion: The proposed automatic technique proved to be reliable for its routine use in a typical eye bank setting like the one considered here.